PERILAKU KONSUMSI MASYARAKAT MUSLIM DI KABUPATEN BONE DALAM MEMILIH MAKANAN HALALAN TOYYIBAN DITINJAU DARI ASPEK PENGETAHUAN DAN RELIGIUSITAS - Fitriani Fitriani; Rina Marlina (FEBI IAI Al Muhammad Cepu, 2022)
This study aims to discuss the consumption behavior of the Muslim community in Bone Regency in choosing halalan toyyiban food in terms of knowledge and religiosity. This is field research with a qualitative approach. The data were obtained from direct interviews with informants, the Muslim community in Bone Regency. To analyze the data that has been collected, the data analysis technique used is the descriptive analysis technique. The results showed that the Muslim community in Bone district had good knowledge of the concepts and characteristics of halalan toyyiban food. Respondents knew well what terms and conditions must be met to be said to be halalan toyyiban, including: the substance, how to get it, how to process it, and how to slaughter it. Animals must comply with Islamic law. From the perspective of religiosity, Muslim people are aware of the importance of halalan toyyiban food, so they are more selective in choosing the food to be consumed.